Refleksy na powierzchni klosza. Otwórczości filmowej Kornela Filipowicza - Lipowski, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
Reflections on the surface of the lampshade. The film works of Kornel Filipowicz This is an overall review of little-known part of artistic creation of Kornel Filipowicz (1913–1990), writer of short stories, novels, scenarios, but also a poet. This reassessment is based on his scenarios, which were created in collaboration with the film director Stanisław Różewicz and his brother, the poet Tadeusz. Informal company formed jointly created ten scenarios completed, Filipowicz participated in the implementation of five titles. The texts discussed in the article mark the major stages in the development of Filipowicz’s writing technique, illustrate his imaginative use of various points of view and of various genres in the construction of film story, and exemplify the wide range of his themes and interests. The article draws also the unpublished screenplay written by Kornel Filipowicz and Stanisław Różewicz Sunset.